E-Health Monitoring System using Wireless Sensor Network - Abdur Rauf Magrabi, Syed (Discoveries in Agriculture and Food Sciences, 2014)
This paper describes about the E-Health monitoring system by using a wireless sensor network. It has wide range of application both in industrial based and as well as commercial based sectors. It mainly deals to monitor the health status of a human body from the harmful sickness and illness like systolic Blood pressure (BP), Heart Rate (HR), Respiratory rate (RR) and temperature of the human body. The necessary equipment and protocols used to monitor the healthy status of the human body are Sensors, communication protocol (TCP/IP), sensor nodes, UML studio and programming in visual basics. The type of platform and the communication based services are used is as follows: Temperature with Publish-Subscribe based service. The compiler used to adjust the range of values for the patient is VISUAL BASICS. The platform used as a sensor node is CorTemp (Core Body Temperature monitoring system)